Cloning, characterization, and functional expression of acs, the gene which encodes acetyl coenzyme A synthetase in Escherichia coli. - Kumari, S (1995)
Acetyl coenzyme A synthetase (Acs) activates acetate to acetyl coenzyme A through an acetyladenylate intermediate; two other enzymes, acetate kinase (Ack) and phosphotransacetylase (Pta), activate acetate through an acetyl phosphate intermediate. We subcloned acs, the Escherichia coli open reading frame purported to encode Acs (F. R. Blattner, V. Burland, G. Plunkett III, H. J. Sofia, and D. L. Daniels, Nucleic Acids Res. 21:5408-5417, 1993). We constructed a mutant allele, delta acs::Km, with the central 0.72-kb BclI-BclI portion of acs deleted, and recombined it into the chromosome. Whereas wild-type cells grew well on acetate across a wide range of concentrations (2.5 to 50 mM), those deleted for acs grew poorly on low concentrations (< or = 10 mM), those deleted for ackA and pta (which encode Ack and Pta, respectively) grew poorly on high concentrations (> or = 25 mM), and those deleted for acs, ackA, and pta did not grow on acetate at any concentration tested. Expression of acs from a multicopy plasmid restored growth to cells deleted for all three genes. Relative to wild-type cells, those deleted for acs did not activate acetate as well, those deleted for ackA and pta displayed even less activity, and those deleted for all three genes did not activate acetate at any concentration tested. Induction of acs resulted in expression of a 72-kDa protein, as predicted by the reported sequence. This protein immunoreacted with antiserum raised against purified Acs isolated from an unrelated species, Methanothrix soehngenii. The purified E. coli Acs then was used to raise anti-E. coli Acs antiserum, which immunoreacted with a 72-kDa protein expressed by wild-type cells but not by those deleted for acs. When purified in the presence, but not in the absence, of coenzyme A, the E. coli enzyme activated acetate across a wide range of concentrations in a coenzyme A-dependent manner. On the basis of these and other observations, we conclude that this open reading frame encodes the acetate-activating enzyme, Acs.